Evaluation of "Spin" in the Abstracts of Systematic Reviews and Meta-Analyses of Therapeutic Interventions Published in High-Impact Plastic Surgery Journals: A Systematic Review. (25th April 2022) - Gallo, Lucas; Yuan, Morgan; Gallo, Matteo; Chin, Brian; Huynh, Minh N Q; McRae, Mark; McRae, Matthew; Coroneos, Christopher J; Thoma, Achilleas; Voineskos, Sophocles H
Abstract: Background: "Spin" is a form of reporting bias where there is a misappropriated presentation of study results, often overstating efficacy, or understating harms. Abstracts of systematic reviews (SRs) in other clinical domains have been demonstrated to employ spin, which may lead to clinical recommendations not justified by the literature. Objectives: The authors sought to determine the prevalence of spin strategies in abstracts of plastic surgery SRs. Methods: A literature search was conducted in MEDLINE, Embase, and CENTRAL to identify all SRs published in the top 5 plastic surgery journals from 2015 to 2021. Screening, data extraction, and spin analysis were performed by 2 independent reviewers. Data checking of the spin analysis was performed by a plastic surgery resident with graduate-level training in clinical epidemiology. Results: From an initial search of 826 SRs, 60 SRs and meta-analyses were included in this study. Various types of spin were identified in 73% of SR abstracts (n = 44). "Conclusion claims the beneficial effect of the experimental treatment despite high risk of bias in primary studies" was the most prevalent type of spin and was identified in 63% of SRs (n = 38). There were no significant associations between the presence of spin and study characteristics. Conclusions: This study found that 73% of abstracts in plastic surgery SRs contain spin. Although systemic reviews represent the highest level of evidence, readers should be aware of types of "spin" when interpreting results and incorporating recommendations into patient care.